EKSPLORASI RUANG KOMUNAL DAN INFORMAL DI KEHIDUPAN KAMPUNG KOTA JAKARTA DALAM PROYEK BALAI BUDAYA KOLEKTIF DAN ANAK PASEBAN - Olivia Nadya; Suryono Herlambang (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
As a combination of Kota (formal city) and Kampung (traditional village), the ‘taste’ of Jakarta can be found in urban villages where many residents formed strong communities. The community produces a new typology that will continue to change and develop according to the adaptability of its citizens. By viewing shared space or commons as an important element of living in cities, urban village development should focus on this commons, in which has a meaning on the use of space, civil society culture, and infrastructure as a process of aligning various urban daily life paths. Urban villages are an example where the practice of shared space is found in daily life. With a narrative architectural exploration method approach based on the scenarios of people's daily lives, the spaces that are formed will become a 'second home' for local residents and also a Third Place’ for its users. The 'Paseban Collective Culture and Children Hall’ Project provides a designated public space, for residents of Kampung Kramat Sawah and Kramat Lontar in Paseban Village, Senen District, based on community participation in socio-cultural-recreational aspects which can also provide non-formal education and productive economic livelihood for its citizens through community empowerment. So that urban villages are  not only as a social production space for habitats, but are also economically productive, according to its local character.  Keywords: Community Empowerment; Community Hall; Informal Social Space; Third Space; Urban Village AbstrakSebagai perpaduan antara Kota (kota formal) dan Kampung (desa tradisional), ‘rasa’ kota Jakarta dapat ditemukan di kampung-kampung kota dimana banyak penduduk membentuk komunitas yang kuat. Komunitas tersebut menghasilkan sebuah tipologi baru yang akan terus berubah dan berkembang sesuai adaptivitas warganya. Dengan memandang ruang komunitas bersama sebagai elemen penting berkehidupan di kota, perkembangan kampung kota seharusnya berfokus pada ruang bersama ini, yang memiliki makna pada: penggunaan ruang, budaya masyarakat sipil, dan prasarana sebagai proses menyelaraskan berbagai jalan hidup sehari-hari perkotaan. Kampung kota menjadi contoh dimana praktik ruang bersama ini banyak ditemukan dalam kehidupan sehari-hari.  Dengan pendekatan metode eksplorasi arsitektur naratif yang berdasarkan skenario kehidupan sehari-hari para warga, ruang-ruang yang terbentuk akan menjadi ‘rumah kedua’ bagi warga lokal dan juga menjadi Ruang Ketiga bagi para penggunanya. Proyek 'Balai Budaya Kolektif dan Anak Paseban' memberikan ruang bersama publik terancang, bagi warga Kampung Kramat Sawah dan Kramat Lontar di Kelurahan Paseban, Kecamatan Senen, berdasarkan partisipasi komunitas dalam aspek sosial-budaya-rekreasional yang juga dapat memberikan edukasi non-formal dan penghidupan ekonomi produktif bagi warganya melalui pemberdayaan komunitas. Sehingga dapat diraihnya kampung yang selain sebagai ruang produksi sosial habitat, tetapi juga produktif secara ekonomi, sesuai dengan karakter kelokalannya.